Detection of methicillin-resistant staphylococcus aureus and extended-spectrum beta-lactamase producers from ready-to-eat roasted beef in Ibadan north, Nigeria. (2021)
Ready-to-eat roasted beef popularly called `Suya' in Nigeria is a highly nutritive food and hence, prone to microbial contamination when handled in an unhygienic manner by the vendors. Extended-spectrum beta-lactamase (ESBL) producers and methicillin-resistant Staphylococcus aureus have been reported in both community and hospital settings in Nigeria. This study investigated their occurrence as microbial contaminants in ready-to eat roasted beef in Ibadan North local government area (LGA) of Oyo state, Nigeria. Fifty (50) samples were purposively collected randomly in four different locations in Ibadan North LGA from 1st to 31st of November, 2019. Aerobic and coliform bacterial counts, isolation, identification and antibiotic susceptibility testing were done using standard microbiological techniques. Phenotypically, methicillin resistant Staphylococcus aureus was detected by cefoxitin-disc-diffusion and ESBL-producers by double-disc synergy. MecA/C and selected ESBL (TEM, SHV and CTX-M) genes were detected by PCR technique. The mean total aerobic and coliform bacterial counts ranged from 1.5 × 106 to 7.8 × 106 cfu/g and 0.8 × 102 to 1.3 × 103 cfu/g respectively. Thirty-eight (38) bacteria were isolated: Staphylococcus aureus (15.8%), Pseudomonas spp. (42.1%), Klebsiella spp. (36.8%) and Bacillus spp. (5.3%). Four (66.7%) of the Staphylococcus aureus were MecA mediated methicillin-resistant strains and 20 (66.7%) of the Gram-negatives were ESBL-producers with 9 (30%) harbouring TEM and SHV and 15 (50%) CTX-M genes. Occurrence of MRSA and ESBL-producers in ready-to-eat roasted beef in Ibadan north is of serious public health concern. Policy and Practice.